Selective toxicity of persian gulf sea cucumber holothuria parva on human chronic lymphocytic leukemia b lymphocytes by direct mitochondrial targeting - Salimi, Ahmad; Motallebi, Abbasali; Ayatollahi, Maryam; Seydi, Enayatollah; Mohseni, Ali Reza; Nazemi, Melika; Pourahmad, Jalal (Environmental toxicology, 2017)
ABSTRACT Natural products isolated from marine environment are well known for their pharmacodynamic potential in diversity of disease treatments such as cancer or inflammatory conditions. Sea cucumbers are one of the marine animals of the phylum Echinoderm. Many studies have shown that the sea cucumber contains antioxidants and anti‐cancer compounds. Chronic lymphocytic leukemia (CLL) is a disease characterized by the relentless accumulation of CD5+ B lymphocytes. CLL is the most common leukemia in adults, about 25–30% of all leukemias. In this study B lymphocytes and their mitochondria (cancerous and non‐cancerous) were obtained from peripheral blood of human subjects and B lymphocyte cytotoxicity assay, and caspase 3 activation along with mitochondrial upstream events of apoptosis signaling including reactive oxygen species (ROS) production, collapse of mitochondrial membrane potential (MMP) and mitochondrial swelling were determined following the addition of Holothuria parva extract to both cancerous and non‐cancerous B lymphocytes and their mitochondria. Our in vitro finding showed that mitochondrial ROS formation, MMP collapse, and mitochondrial swelling and cytochrome c release were significantly (P < 0.05) increased after addition of different concentrations of H. parva only in cancerous BUT NOT normal non‐cancerous mitochondria. Consistently, different concentrations of H. parva significantly (P < 0.05) increased cytotoxicity and caspase 3 activation only in cancerous BUT NOT normal non‐cancerous B lymphocytes. These results showed that H. parva methanolic extract has a selective mitochondria mediated apoptotic effect on chronic lymphocytic leukemia B lymphocytes hence may be promising in the future anticancer drug development for treatment of CLL. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1158–1169, 2017.